2020
DOI: 10.1177/0272989x20977885
|View full text |Cite
|
Sign up to set email alerts
|

Observer Ratings of Shared Decision Making Do Not Match Patient Reports: An Observational Study in 5 Family Medicine Practices

Abstract: Background Measuring shared decision making (SDM) in clinical practice is important to improve the quality of health care. Measurement can be done by trained observers and by people participating in the clinical encounter, namely, patients. This study aimed to describe the correlations between patients’ and observers’ ratings of SDM using 2 validated and 2 nonvalidated SDM measures in clinical consultations. Methods In this cross-sectional study, we recruited 238 complete dyads of health professionals and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…feel more room to make the medical decision themselves when physicians show more SDM behaviour. The discrepancy that we observed between how patients perceived the decision-making role in consultations and the observed patient involvement as assessed by an independent researcher using the validated OPTION5 instrument expands those of previous studies in selected care centres with doctors trained in SDM [16][17][18][19][20][21][22][23]. It should be noted that these two instruments (CPS and OP-TION5) were designed for different purposes, and none of the studies comparing results from these instruments (including our own) have investigated or confirmed that they capture comparable aspects of the decision-making process as perceived by patients (CPS) or independent observers (OPTION5).…”
Section: Tablesupporting
confidence: 66%
See 1 more Smart Citation
“…feel more room to make the medical decision themselves when physicians show more SDM behaviour. The discrepancy that we observed between how patients perceived the decision-making role in consultations and the observed patient involvement as assessed by an independent researcher using the validated OPTION5 instrument expands those of previous studies in selected care centres with doctors trained in SDM [16][17][18][19][20][21][22][23]. It should be noted that these two instruments (CPS and OP-TION5) were designed for different purposes, and none of the studies comparing results from these instruments (including our own) have investigated or confirmed that they capture comparable aspects of the decision-making process as perceived by patients (CPS) or independent observers (OPTION5).…”
Section: Tablesupporting
confidence: 66%
“…It has been well established that most patients prefer SDM, [15,16] but there is scant literature on how patients perceive the actual decision-making process in everyday clinical practice. The available studies that investigated patient perception of decision making in consultations were conducted in specific settings (such as breast cancer or dialysis care) and the participating physicians in these studies were either trained in SDM or worked in a department running an SDM implementation program [16][17][18][19][20][21][22][23]. Thus, patients' perceptions of the decision-making process in everyday clinical practice encounters are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although SDM-Q-Doc and SDM-Q-9 scores differ widely throughout literature, these positive perceptions are consistent with previous studies. 31–33 The three instruments intend to capture different perspectives on SDM performance: observable behaviour and residents’ and patients’ experiences with the applied behaviour. Contrasting perceived and observed consultation performance, and learners becoming aware of potential incongruences, may be an important stimulus for fostering motivation to learn SDM.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, research also establishes the effects of training on behaviour of oncologists in the clinical setting and on patient outcomes [ 14 , 20 ], including both observer and patient-reported outcomes. Since the patient may experience more involvement than observers recognise [ 36 ], different methods, e.g. conversation analysis [ 37 ], or different instruments, e.g.…”
Section: Discussionmentioning
confidence: 99%